KONSEP PENDIDIKAN KELUARGA DALAM SURAT LUQMAN AYAT 12-19 - Iwan Aprianto (P3M IAI Nusantara Batang Hari, 2016)
Education is a critical need for each country, thegovernment in general and schools in particular.Religious education is more important whereas the roleof parents of children is essential during the children‟searly education. Thus the first form of education presentin family life. Education is nothing but emphasized theconcept of Islamic education which makes the problem ofservitude to God and obedience to Him become the axisof all life. It should be noted also that the child's physicaleducation is included in the integral part and theeducation of the soul, mental, and personality. Duties ofparents in educating children from childhood is going tointroduce children the Lord that create and administerthe universe, understand who is the prophet, andunderstand what is their religion, so that childrenunderstood the responsibility living in this world, whichis to worship Allah alone by following the sunnah of HisMessenger. It is obvious, that Islam tells them to carryout the education of their children, based on the viewthat children as beings who are growing and developingin the direction of maturity, have the basic skills whichare dynamic and responsive to external influences andhimself.